2011
DOI: 10.1111/j.1365-294x.2011.05393.x
|View full text |Cite
|
Sign up to set email alerts
|

Propagule pressure and colony social organization are associated with the successful invasion and rapid range expansion of fire ants in China

Abstract: We characterized patterns of genetic variation in populations of the fire ant Solenopsis invicta in China using mitochondrial DNA sequences and nuclear microsatellite loci to test predictions as to how propagule pressure and subsequent dispersal following establishment jointly shape the invasion success of this ant in this recently invaded area. Fire ants in Wuchuan (Guangdong Province) are genetically differentiated from those found in other large infested areas of China. The immediate source of ants in Wuchu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 81 publications
(187 reference statements)
0
23
0
Order By: Relevance
“…It is generally accepted that introduction events can be accompanied by founder events and that associated loss of genetic diversity may result in inbreeding depression, which could reduce ability of the invasive species to adapt to its new environment. However, there have been several cases of introduced populations with low genetic diversity (genetic bottlenecks) that have been successful (ant Linepithema humile: Tsutsui et al 2000;Yang et al 2012;mosquitofish Gambusia affinis: Purcell et al 2012 (Weir and Cockerham 1984). Below diagonal: D est , bias-corrected differentiation index (Jost 2008 c Bayesian individual clustering of Crassostrea gigas performed in STRUCTURE, using the admixture model with correlated allele frequencies, and using sample group information (Hubisz et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that introduction events can be accompanied by founder events and that associated loss of genetic diversity may result in inbreeding depression, which could reduce ability of the invasive species to adapt to its new environment. However, there have been several cases of introduced populations with low genetic diversity (genetic bottlenecks) that have been successful (ant Linepithema humile: Tsutsui et al 2000;Yang et al 2012;mosquitofish Gambusia affinis: Purcell et al 2012 (Weir and Cockerham 1984). Below diagonal: D est , bias-corrected differentiation index (Jost 2008 c Bayesian individual clustering of Crassostrea gigas performed in STRUCTURE, using the admixture model with correlated allele frequencies, and using sample group information (Hubisz et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In Longyan city, H36 was much less common than H5 (23% and 77%, respectively) (Fig. , also see previous research data in China from Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Our results, being consistent with conclusions of recent works that reconstructed invasion pathways of S. invicta (Ascunce et al ., ; Yang et al ., ), showed that S. invicta populations in China most likely originated from the USA but not from its native range. Importantly, the fact that no new haplotypes were detected in China likely suggests that the expanding distribution of S. invicta within China, at least to Fujian Province, mainly resulted from spreads from existing populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations